Assessing Health Literacy of Elderly with Chronic Diseases during the COVID-19 Pandemic in Makassar City, Sulawesi Selatan, Indonesia - Bahtiar, Bahtiar; Saputri, Wiwi; Paseleng, Roastika Salenda; Akbar, Muh; Abady, Restu (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
The elderly are vulnerable to experience health problems and physical deterioration characterized by highrates of chronic diseases among the elderly. Health literacy ability becomes crucial for the elderly withchronic diseases to treat and maintain their health. This study was aimed to describe the literacy levels of theelderly with chronic diseases during the COVID-19 pandemic in Makassar. The method of study was adescriptive survey with a cross-sectional study. The research population is elderly with chronic diseases inMakassar city, and the samples are 124 elderly with age ≥60 years old and suffering chronic diseases morethan six months in two selected sub-district. The research was conducted a cross-sectional survey, anddescriptive univariate data analysis was used. The instrument was used Indonesia's health literacy shortform survey questionnaire (HLS-EU-SQ10-IDN). The result of this study reveals that the health literacylevels vary: insufficient criteria by 33.99%, problematic criteria by 49.2%, sufficient criteria by 16.1%, andperfect criteria by 0.8%. The results prove that the health literacy level of the elderly with chronic diseases isinsufficient. This study concluded that the dominant level of the health literacy of the elderly with chronicdiseases is inadequate and problematic. Health education program to improve their literacy is necessarilyimproved during the COVID-19 outbreak.